Flexural behaviour of brick masonry retrofitted with braided textile meshes - Vasconcelos, Graça (2013)
The vulnerability of unreinforced masonry walls (URM) under seismic events, causing huge loss of money and human lives, has revealed the enormous need for an efficient strengthening material. In this context, the present paper reports the development of a new reinforcing material for masonry walls based on braided fibrous structures. These fibrous materials were developed through braiding of polyester yarns around a core made of either glass fiber (core reinforced braid). Masonry walls were fabricated by placing these braided materials on the surface of clay brick walls in a mesh like configuration and covering with a mortar layer. This technique is designated as reinforced textile mortar retrofitting technique.